Arizona Cultural Inventory Project Usage: A Case Study - Ringness, Allison (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
The purpose of this study is to identify usage patterns of the Arizona Cultural Inventory Project (CIP), a directory of cultural institutions.  The author analyzed quantitative web log statistics collected from the website over a 16-week period, and found that the website was visited 2,073 times.  Furthermore, the average visitor was located in Phoenix, Arizona, and accessed the website via a desktop computer.